Association of Magnet Status and Nurse Staffing With Improvements in Patient Experience With Hospital Care, 2008–2015. Issue 2 (February 2018) - Zhu, Junya; Dy, Sydney M.; Wenzel, Jennifer; Wu, Albert W.
Abstract : Background: Little is known about the longitudinal association of hospital Magnet status (an indicator of nursing excellence) and nurse-staffing level with inpatient care experience. Objectives: To examine temporal trends in hospital performance on patient experience measured using the Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey and the association of these trends with Magnet status and nurse-staffing level. Research Design: Longitudinal study of hospital-level data from the HCAHPS survey, the American Hospital Association Annual Survey, and the American Nurses Credentialing Center. Growth curve models were used for the analysis of longitudinal associations. Subjects: A total of 26, 752 hospital-year observations from 3614 US hospitals that collected at least 3 years of HCAHPS data from patients discharged between 2008 and 2015. Measures: Dependent variables were 7 HCAHPS measures. Independent variables included linear and quadratic time terms, hospital Magnet status, and nurse-staffing level. Results: There were significant improvements ( P <0.001) in all 7 HCAHPS measures, but the trends were nonlinear; the improvement rates have decreased over time. Magnet hospitals and hospitals with more favorable nurse staffing consistently performed better on HCAHPS but did not improve faster than other hospitals during the study period. In subgroup analyses, HCAHPS scores did not improve for hospitals after they received Magnet recognition during the period from 2009 to 2015. Conclusions: The hospital organizational attributes that lead to Magnet recognition or better nurse staffing may be associated with higher performance on HCAHPS. Magnet status and favorable nurse staffing may be markers of hospital commitment to better patient-centered care. Abstract : Supplemental Digital Content is available in the text.